Kim - Kipling, Rudyard, 1865-1936. (Mattituck, N.Y. : American Reprint, 1901)
Kim's early years as an orphaned beggar in India lead to an exciting career in the British Secret Service.
Includes bibliographical references (p. 263-265).
Young Adult
Young Adult
940
Keywords: India -- History -- 19th century -- Fiction; Spies -- Fiction; India -- History -- Fiction; Spy stories; Adventure fiction